Linking Multimodal Communication and Feedback Loops to Reinforce Plagiarism Awareness - O'Donnell, Kerri (Business communication quarterly, 2011)
In this article, the author describes the use of an electronic quiz on a trial basis as a means of improving students' awareness of academic misconduct issues and their understanding of how to avoid those issues. The quiz integrated several new factors into information-sharing processes, increasing feedback to both students and staff. It was by no means a sophisticated instrument, but a surprising change in student behaviours, in comparison with past semesters, suggests that further research and development may be useful. The quiz was not intended as the sole means of communicating about academic integrity. Rather, its purpose was to supplement information provided in a unit outline (UO) document and talked about at lectures and tutorials during introduction to, and explanation of, assignment requirements, as well as supplementary written documentation and web links providing tips and techniques for successful study in general. Furthermore, the quiz required students to answer questions with reference to the previously provided written and verbal information, so that they would consciously consider that information. The quiz was delivered to 206 students enrolled in a management accounting subject (unit), a full-semester component of a postgraduate conversion course designed as a pathway for entry to the professional programs of Australia's accounting bodies. Results were encouraging, with far fewer cases of suspected plagiarism than in previous semesters and less than 5% (10/206) of Assignment 1 papers referred for determination. No papers were reported for copying/pasting from the Internet or other published sources. Almost every student provided a reference list (whether warranted or not), and most referenced in-text. While further technical improvement was necessary in most cases, this suggests that students can, and will, learn referencing if they recognise it as necessary.